FEIBA versus NovoSeven in Hemophilia Patients with Inhibitors - Franchini, Massimo; Coppola, Antonio; Tagliaferri, Annarita; Lippi, Giuseppe (Seminars in Thrombosis and Hemostasis, 2013)
The management of patients with congenital hemophilia who develop alloantibodies that neutralize coagulation factor activity is the most important challenge for hemophilia care providers because this complication renders replacement treatment with factor concentrates partially or completely ineffective, exposing the patients to an increased risk of morbidity and mortality. Development of inhibitors complicates the clinical course of severe hemophilia in up to 30% of patients with hemophilia A and up to 5% of those with hemophilia B. Although the ultimate goal of treatment of patients with alloantibodies against factors VIII and IX is eradication of the inhibitor, the control of bleeding through high doses of factor concentrates (low titer inhibitors) or bypassing agents (high titer inhibitors) is the mainstay of management of these patients. In this review, we summarize the main characteristics of the bypassing agents FEIBA and NovoSeven, briefly discussing available literature data, and in particular, focusing on comparative studies.
Keywords: FEIBA; NovoSeven; bypassing agents; inhibitors; alloantibodies; congenital hemophilia; bleeding